Driving forces behind latitudinal variations in plant-herbivore interactions in SW Atlantic salt marshes - Canepuccia, Alejandro Daniel (2018)
Despite long-standing interest in the hypothesis that strength of plant-herbivore interactions decreases at higher latitude, supporting evidence is scarce and the data is conflicting. By field survey and two experiments we examined this hypothesis focusing on the herbivory by the stem-borer moth (Haimbachia sp. nov.) on the dominant SW-Atlantic marsh grasses (Spartina alterniflora and S. densiflora). Field surveys indicate that herbivore abundances and damage, although tending to decrease simultaneously, are unrelated to latitude. Herbivore abundances were related to latitude-dependent variables such as day length and temperature, and also to latitude-independent variables such as precipitation, salinity, and tide amplitude. Abundances were indirectly related to the effects of these variables and sediment characteristics on plant traits like density, height and tissue-composition. After 33-months, herbivore abundances and damage of high-latitude plants transplanted to low-latitude were 50-times greater than plants transplanted from low-to high-latitude sites. In a common-garden experiment (38º 56´ S) without herbivore pressure, differences persisted in plant traits from high and low latitude suggesting lack of herbivore induced effects on these plant traits. The persisting conspecific differences in plant-traits translocated along latitude suggest that these variations are under genetic control. Thus, our results provide evidence that although plant-herbivory interactions are more important at lower latitude, many additional and contingent variables unrelated with latitude can divert this geographic pattern.